Hemoglobin glycation index and neutrophil percentage as predictors of congestive heart failure among individuals diagnosed with sepsis: A MIMIC-IV cohort study - Qijia Feng; Yufei Ma (Scientific Reports)
Abstract This study aimed to investigate the link between a combined indicator—hemoglobin glycation index (HGI) coupled with neutrophil percentage—and the risk of congestive heart failure (CHF) among patients suffering from sepsis. Adult individuals (aged 18 or older) diagnosed with sepsis and undergoing their initial intensive care unit stay lasting over one day were identified from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database for analysis. The combined indicator—integrating HGI and neutrophil percentage—was grouped into quartiles, labeled Q1 to Q4. The cumulative incidence curves were employed to evaluate the association between this combined indicator and the risk of developing CHF. We carried out Kaplan-Meier (KM) analysis, constructed multivariable Cox regression models, and conducted restricted cubic spline (RCS) analysis for elucidating the association between HGI/neutrophil percentage/the combined indicator and the risk of in-hospital mortality, examining the potential association between HGI/the combined indicator and the risk of CHF, and determining the link between HGI and CHF risk, respectively. 11,089 patients were included, with a CHF incidence of 30.43% in the sepsis cohort. Cumulative incidence analysis indicated that patients with higher levels of the combined indicator exhibited a notably elevated risk of CHF versus those with lower levels (P < 0.0001). KM survival curves demonstrated that elevated levels of the combined indicator or HGI were linked to an elevated in-hospital mortality risk (P < 0.0001). Relative to patients in the combined indicator-Q1, those in Q2, Q3, and Q4 demonstrated an increased risk of CHF, as determined by Cox proportional hazards regression analysis. Higher HGI levels remained significantly linked to elevated CHF risk, as confirmed by multivariable Cox regression analysis. According to the multivariable Cox regression forest plot, patients classified in Q3 of the combined indicator was associated with a higher risk of developing CHF, whereas lower risk was observed among individuals aged ≤ 65 and those who were married. RCS analysis suggested that although the relationship between HGI (ranging from − 3 to 3) and CHF was not strictly linear, higher HGI was associated with an elevated risk of CHF (HR > 1). In critically ill patients with sepsis, the combined indicator (comprising HGI and neutrophil percentage) is an independent risk factor for CHF, showing a significant association with elevated CHF risk.